2021
DOI: 10.1002/adsc.202101166
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine‐Catalyzed Annulations of Quinone Monoacetals with Naphthols: Synthesis of 2‐Oxabicyclo[3.3.1]nonane Skeletons, Transformations and Reaction Mechanism

Abstract: Herein, we report the pyrrolidine‐catalyzed annulation reaction of p‐quinone monoacetals with naphthols at room temperature. The reaction is also extended to including 4‐hydroxycoumarin, 4‐hydroxy‐1‐methylcarbostyril, 4‐hydroxycarbostyril, and several β‐ketoesters as the nucleophiles, thereby providing a collection of bridged cyclic compounds bearing 2‐oxabicyclo[3.3.1]nonane skeletons in 41–96% yields. The reaction can be adapted to gram‐scale synthesis, and several transformations of the obtained bridged cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…In addition, Büchi and Grieco also reported examples of cationic [5+2] cycloaddition of alkenes with specific types of p ‐QMAs that bear alkyoxyl groups at β‐C position to offer bicyclo[3.2.1] ring compounds [11] . On the other hand, based on an iminium catalysis strategy, we recently realized the selective annulation of p ‐QMAs with naphthols for the synthesis of aryl‐fused oxabicyclo[3.3.1]nononoids (Scheme 1B, c) [8h] . The method was successfully expanded to the use of 4‐hydroxycoumarin, 4‐hydroxycarbostyril, 4‐hydroxy‐1‐methylcarbostyril and β‐ketoesters as nucleophiles, affording several types of heteroaryl‐fused bridged‐ring skeletons.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Büchi and Grieco also reported examples of cationic [5+2] cycloaddition of alkenes with specific types of p ‐QMAs that bear alkyoxyl groups at β‐C position to offer bicyclo[3.2.1] ring compounds [11] . On the other hand, based on an iminium catalysis strategy, we recently realized the selective annulation of p ‐QMAs with naphthols for the synthesis of aryl‐fused oxabicyclo[3.3.1]nononoids (Scheme 1B, c) [8h] . The method was successfully expanded to the use of 4‐hydroxycoumarin, 4‐hydroxycarbostyril, 4‐hydroxy‐1‐methylcarbostyril and β‐ketoesters as nucleophiles, affording several types of heteroaryl‐fused bridged‐ring skeletons.…”
Section: Methodsmentioning
confidence: 99%
“…14 16 For example, Qu et al reported the three-component couplings of pyrrolidin-3-ol and p -benzoquinone monoacetal with vinyl- and arylboronic acids to selectively afford cis -2-substituted 3-pyrrolidinols. 16a Recently, we 14` e f g h and others 16b c reported a series of transformations involving QMAs, primary amines/amino acids, with/without another nucleophile to afford 3-aminoarylphosphoryl products, N -aryl-2-arylpyrrolidines, octahydrodipyrroloquinolines, and bridged oxocyclic compounds selectively. Here, we report our results on two sets of MCRs involving QEs/QMAs as both the arylation components and the oxidants, and H-phosphine oxides/naphthols as the terminating nucleophiles to accomplish the process of N -arylation of the simple pyrrolidine with α-phosphinylation or arylation.…”
Section: Table 1 Optimization Of Reaction Conditions Fo...mentioning
confidence: 99%
“…In order to obtain the diastereoselective annulation product, subsequently further reported procedures for annulation were examined. Reactions were carried out in the presence of Lewis acids TiCl 4 45 and InCl 3 46 and organocatalysts pyrrolidine 47 and piperidine. 48 In the presence of all these catalysts once again a mixture of diastereomers 7a and 7b were obtained (Table 2, entries 6-9).…”
Section: Scheme 2 Synthesis Of Perlin Aldehydes 4abmentioning
confidence: 99%